Inovasi Aplikasi Whatsapp Dalam Pelayanan Pembuatan Kartu Identitas Anak: Studi Kasus Pada Dinas Kependudukan dan Pencatatan Sipil Kabupatan Tangerang - Muhamad Arham; Udin Syamsudin; TB. Yudi Muhtadi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This study aims to find out how public service innovation is as an effort to improve the quality of public services in making Child Identity Cards (KIA) using the Whatsapp application at the Tangerang Regency Population and Civil Registration Office and to find out the inhibiting factors in the service process for making Child Identity Cards (KIA) in Department of Population and Civil Registration of Tangerang Regency. This type of qualitative descriptive research is used in this study. researchers used a descriptive research pattern. Sources of data used in this study are primary data and secondary data. The data collection methods in this study are as follows, observation, interviews and documentation. The data analysis technique used is data reduction, data display and conclusion. The results of the study show that according to the theory of public service innovation according to Bloch (2010) it is concluded that the product indicators show consistent results. Meanwhile, the process, organizational, and communication indicators show results that are not optimal. Inhibiting factors in improving the quality of services for making Child Identity Cards (KIA) using the WhatsApp application include inadequate facilities and infrastructure, low utilization of technology and low public awareness of MCH ownership.